Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.